2005
DOI: 10.1165/rcmb.2004-0010oc
|View full text |Cite
|
Sign up to set email alerts
|

α-Galactosylceramide, a Ligand of Natural Killer T Cells, Inhibits Allergic Airway Inflammation

Abstract: alpha-Galactosylceramide (alpha-GalCer) is a specific ligand of natural killer T cells (NKT cells) that regulates the immune responses such as tumor rejection and autoimmunity by producing interferon (IFN)-gamma and interleukin (IL)-4. However, it has not been determined whether alpha-GalCer-activated NKT cells modulate allergic inflammation. Because alpha-GalCer induces a large amount of IFN-gamma production by NKT cells, we hypothesized that an in vivo administration of alpha-GalCer could inhibit allergic ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 44 publications
3
64
2
Order By: Relevance
“…␣-GalCer is known to induce iNKT cell anergy in a manner similar to T cells treated with superantigens (18), although ␣-GalCer may also alter other factors such as iNKT cell trafficking or cytokine production to prevent subsequent AHR. The attenuated AHR observed with two doses of ␣-GalCer may be similar to recent reports showing that administration of ␣-GalCer to mice already sensitized to ovalbumin (OVA) prevented the subsequent development of AHR (19)(20)(21). However, in a similar OVA-induced AHR system, we found that administration of ␣-GalCer just before airway challenge with OVA resulted first in exacerbation of AHR, measured 48 h after the ␣-GalCer challenge, although AHR measured 96 h after the ␣-GalCer administration was reduced (Fig.…”
Section: Induction Of Inkt Cell Unresponsiveness Prevents Subsequent supporting
confidence: 88%
See 1 more Smart Citation
“…␣-GalCer is known to induce iNKT cell anergy in a manner similar to T cells treated with superantigens (18), although ␣-GalCer may also alter other factors such as iNKT cell trafficking or cytokine production to prevent subsequent AHR. The attenuated AHR observed with two doses of ␣-GalCer may be similar to recent reports showing that administration of ␣-GalCer to mice already sensitized to ovalbumin (OVA) prevented the subsequent development of AHR (19)(20)(21). However, in a similar OVA-induced AHR system, we found that administration of ␣-GalCer just before airway challenge with OVA resulted first in exacerbation of AHR, measured 48 h after the ␣-GalCer challenge, although AHR measured 96 h after the ␣-GalCer administration was reduced (Fig.…”
Section: Induction Of Inkt Cell Unresponsiveness Prevents Subsequent supporting
confidence: 88%
“…Although we found that administration of ␣-GalCer directly induces AHR, several groups recently found that administration of ␣-GalCer 24 h before challenge with OVA inhibited allergeninduced AHR (19)(20)(21). In contrast, other investigators have found that coadministration of ␣-GalCer with antigen sensitizes mice to these antigens, thereby enhancing AHR (38,39).…”
Section: Discussioncontrasting
confidence: 58%
“…Systemic administration of aGalCer, a specific ligand for iNK-T cells, was shown to prevent the development of allergic airway inflammation and AHR under certain conditions (25,27,28). However, these findings could not distinguish whether the effects were manifested during the initiation phase of the response or specifically altered the subsequent airway response to allergen challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In previously sensitized mice, IFN-g was shown to be critical to the inhibition of allergic airway inflammation and AHR induced by aGalCer (25,27,28). To determine whether transfer of OVA BMDCs exposed to aGalCer modulated the numbers of iNKT cells in the lung and their capacity for IFN-g production, we quantified the number of iNKT cells in the lungs and the numbers of IFN-gproducing iNKT cells by intracellular cytokine staining.…”
Section: Intracellular Cytokine Staining Of Lung Inkt Cellsmentioning
confidence: 99%
See 1 more Smart Citation